2017
DOI: 10.1111/1556-4029.13720
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reliability of Total Body Mass Estimation Techniques from Stature and Bi‐iliac Breadth in Non‐Hispanic U.S. Whites from the Bass Donated Skeletal Collection

Abstract: This paper tests the fidelity of a recent method that used the NHANES III dataset as a proxy to estimate total body mass from stature and bi-iliac breadth in U.S. White males and females. The bi-iliac breadths of 230 males and 152 females identified as non-Hispanic U.S. White from the Bass Donated Skeletal Collection were measured, and along with stature from predonor paperwork, total body mass estimates were calculated and then compared to body masses recorded on predonor paperwork. Male and female samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…The regression modelling was first performed for the full sample because a general population approach with maximal representativeness at the population level was considered beneficial in this forensic context; publishing formulae for body mass estimates derived from an unselected population may be potentially valuable for future forensic practice. However, as previous studies have suggested that equations derived from normal-weight individuals are more accurate than those derived from under/overweight individuals [11,25], we re-ran the analysis among normal-weight individuals only (18.5 ≤ BMI < 25 according to the WHO classification [26]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regression modelling was first performed for the full sample because a general population approach with maximal representativeness at the population level was considered beneficial in this forensic context; publishing formulae for body mass estimates derived from an unselected population may be potentially valuable for future forensic practice. However, as previous studies have suggested that equations derived from normal-weight individuals are more accurate than those derived from under/overweight individuals [11,25], we re-ran the analysis among normal-weight individuals only (18.5 ≤ BMI < 25 according to the WHO classification [26]).…”
Section: Discussionmentioning
confidence: 99%
“…We also generated equations for estimating the body mass of the Finnish population at these two time points. As previous studies [11,25] have indicated that body mass estimations seem to reach highest accuracy among individuals within the normal body mass index (BMI, kg/m 2 ) range (18.5 ≤ BMI < 25 according to the WHO classification [26]), we decided to utilize 1) our entire sample and 2) a subsample that included only individuals with normal BMI at both time points. Our purpose was to investigate how sample selection affects body mass estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Body mass estimation from skeletal remains is difficult because it is composed of both fat-free (lean) mass (muscle, organs, bone) and fat mass. Both mechanical and morphological methods [1][2][3][4][5][6][7][8] are relatively accurate for estimating lean body mass and therefore can be used for nonobese individuals, but body mass estimation errors increase with increasing BMI [9]. As Moore and Schaeffer [2] (p. 1115) note, "the ability to estimate the extremes of body mass (or weight) from the skeleton represents an intellectual gap in osteological analysis.…”
Section: Introductionmentioning
confidence: 99%
“…While most studies examining the relationship between body mass and skeletal morphology have focused on trying to accurately estimate body mass at death, the estimation of the BMI category may be more practical and beneficial for the biological profile, especially if an individual has a history of obesity or emaciation. Body mass for individuals is very difficult to estimate and is usually inaccurate for obese individuals [8,9]. Also, when provided in missing person records the body mass is often missing or only estimated.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is to investigate the accuracy and fidelity of a recent ST-BIB method proposed by Schaffer from a large dataset of modern young adult individuals with healthy body fat percentages in the Third National Health and Nutrition Examination Survey (NHANES III) 1988-1994." [30] Framing previous research/state of the field 13 "In particular, Hefner critiques Rhine by arguing that the trait lists exclude a significant amount of human variation by relying heavily on a typological, experience-based approach that is dependent on extreme trait expressions, which is problematic in light of the high-caliber science and methodological standardization required by the Daubert rulings." [31] Advocating for future research 7 "While historically age estimation was regarded as 'ultimately an art, not a precise science', in the face of Daubert and our current era of validation and scientific rigor, these issues need to be addressed."…”
mentioning
confidence: 99%